Penggunaan Uang Digital dalam Transaksi Keuangan Masyarakat di Desa Jambu Kabupaten Bengkulu Tengah - Yefriza; Ekaputri, Retno Agustina; Pasaribu, Esti; Sitorus, Antoni (Kreativasi : Journal of Community Empowerment, 2024)
This community service activity (PPM) was carried out with the issue of Digital Money in Financial Transactions in Jambu Village, Central Bengkulu Regency. The activity was attended by 20 participants from the Talang Jambu Village Community. This activity was motivated by the fact that many people still do not understand digital money and the distance of public banks from villages means that economic activities are often hampered. In this activity, people can understand the need for technology in finance and payment tools so that economic transactions can continue to be carried out even if they do not have cash. Digital money also makes the transaction process easier because there is no need for direct face-to-face contact between sellers and buyers so economic activity can run more massively and conductively.